Hot air solder levelling (HASL) process parameters optimization for SN100CL - Fatin Afeeqa Mohd Sobri (School of Materials Engineering, 2016)
In this study, the coating thickness that is required for a good solderability will be conducted using Gen3 wetting balance test. In phase I of study, initial coating process optimization of coating dipping time using copper strips with dimension of 10 mm (length) X 3 mm (width) X 0.3 mm (thickness). For determining the relationship between interfacial IMC, free solder thickness and coating thickness, accelerated aging test are conducted and cross section were observed under SEM. The thickness of interfacial IMC, free solder thickness and coating thickness are measured by J-image software. A plotted graph is constructed to observe the relationship of the thickness versus aging time.